Displacement Measurements of Three Slow Moving Landslides at Almenningar, North Iceland. A Feature Tracking Application. - Elías Arnar Nínuson 1994- (2023)
The Siglufjarðarvegur road is an important transportation route in north Iceland. This road cuts through the Almenningar area where three active slow moving landslides are situated, these are the Tjarnadalir, Þúfnavellir and Hraun landslides. The constant activity of these landslides affects a 5-6 km long stretch of the road that poses a problem in terms of safety and maintenance. Previous studies have mainly focused on the northernmost Tjarnadalir landslide as movement rates appear to exceed 1 m/yr for some periods. This is also the case for the southernmost Hraun landslide but the Þúfnavellir landslide in the middle is moving at a slower rate. The landslides are characterized by constant motion with periods of increased activity in between. GPS measurements have been conducted on a yearly basis in the area but these are limited to a certain number of points that are all situated along the road. Little is known about the different movement rates within the landslide bodies themselves. The aim of this study is therefore to provide a spatial and temporal overview of the movement rate within the area through the application of remote sensing. Digital image comparison was conducted with the feature tracking method in order to estimate the rate of movement throughout the entirety of all three landslide bodies. Available data extends back to the year 1954 to present day, giving an unprecedented insight into the temporal and spatial dynamics of the landslides. Main findings show that there is spatial variation in movement rate within all three landslides and the velocity of the movement changes through time. Some of the highest displacement values were measured for the time periods from 1994 - 2000 and between 2016 - 2022, indicating an increase in velocity. Precipitation and spring thawing are considered key controlling factors of the displacement rate, suggesting that climate change could increase the unpredictability of this hazard in the future. The study provides important findings that benefit risk mitigation ...